Biomechanical analysis of ponte osteotomy and PSO osteotomy in the treatment of ankylosing spondylitis with thoracolumbar kyphotic deformity - Zhu, Xu; Yusufu, Alimujiang; Waisiding, Ajiguli; Ma, Yuan (Frontiers in Surgery, 2026)
BackgroundAnkylosing spondylitis (AS) commonly progresses to thoracolumbar kyphosis. Pedicle subtraction osteotomy (PSO) and Ponte osteotomy are frequently used surgical methods. However, systematic comparative biomechanical studies of these two methods are insufficient, and differences in postoperative mechanical complication risks remain unclear.ObjectiveTo compare the biomechanical characteristics of Ponte and PSO osteotomies in the treatment of AS with thoracolumbar kyphotic deformity, providing a biomechanical basis for clinical surgical decision-making.MethodsFinite element models representing unresected (M0), Ponte osteotomy (M1), and PSO osteotomy (M2) conditions were constructed based on CT data from an AS patient. A vertical load of 500 N and moments of 10 N·m in each direction were applied to the T3 vertebral body. Six loading conditions, including flexion and extension, were simulated. Spinal range of motion (ROM), vertebral stress, internal fixation stress, and displacement were analyzed.ResultsModel validation showed that ROM of M0 was consistent with previous studies. After surgery, ROM significantly decreased in both osteotomies compared with M0, with M2 showing lower ROM than M1. In the M1 model, stress in the T3–T5 vertebral bodies decreased, but stress in T6 did not significantly change. In the M2 model, stress in T4–T5 vertebral bodies decreased, while stress in T7–T8 increased. Internal fixation stress in M1 was significantly lower than in M2 across all loading conditions, although displacement was greater in M1.ConclusionPonte osteotomy distributes stress across multiple segments, reducing internal fixation load, and is therefore suitable for moderate kyphotic deformities. PSO osteotomy provides superior corrective capability but concentrates stress on distal vertebral segments, making it suitable for severe deformities. These results can guide clinical decisions for individualized surgical selection.